2 % - Hadjimitsis, Diofantos G. (My University, 2026)
https://www.cut.ac.cy/news/article/?contentId=536640 LAST 5 YEARS 2025, 2024, 2023 ETC https://top2percentscientists.com/
Keywords: Worlds Top Scientists